2021
DOI: 10.1007/s12144-021-01480-6
|View full text |Cite|
|
Sign up to set email alerts
|

Research on the reform of management system of higher vocational education in China based on personality standard

Abstract: With the rapid development of Higher Vocational Education in China, the main objective is to improve the quality of Higher Vocational Education in an all-round way. For a long time, higher vocational education has been using the knowledge-based education mode of general higher education or secondary vocational education. Until the early 1990s, the ability-based education model was gradually introduced. The understanding and research of higher vocational education should not be confined to the interior of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…At present, higher education management has gradually changed into the core component of various colleges and universities. With the gradual deepening of higher education system reform, the traditional higher education management system cannot keep up with the progress of modern education [1][2][3]. Nowadays, the educational measures of higher education institutions have been gradually implemented, and the source of students in higher education institutions is growing steadily, which brings a greater burden to the teaching management system.…”
Section: Introductionmentioning
confidence: 99%
“…At present, higher education management has gradually changed into the core component of various colleges and universities. With the gradual deepening of higher education system reform, the traditional higher education management system cannot keep up with the progress of modern education [1][2][3]. Nowadays, the educational measures of higher education institutions have been gradually implemented, and the source of students in higher education institutions is growing steadily, which brings a greater burden to the teaching management system.…”
Section: Introductionmentioning
confidence: 99%
“…Research also reveals that Chinese high school Technical and Vocational Education (TVE) yields relatively high private returns, particularly for academically underperforming students [12] . To better promote the development of higher vocational education, China needs to explore research from multiple disciplines and perspectives, including socioeconomic, technological industry, historical-cultural, and management policies [13] . German and Chinese vocational education and training schools exhibit both similarities and differences in teaching traditions, classroom organization, and modern media usage [11] .…”
Section: Transnational Comparison Of Vocational Education Systemsmentioning
confidence: 99%
“…Thus, it is indicated that higher vocational education has significant developments, including expanding use of technology, the increasing relevance of information and communications systems, and changes in national demography, characterising vocational education and training around the world. In addition, with the rapid development of higher vocational education, the critical goal is to increase overall quality (Ling, Jeong, & Wang, 2021). For a long time, higher vocational education has used the knowledge-based education paradigm of general higher education.…”
Section: Network Visualisation Map Of Authors' Abstractmentioning
confidence: 99%